Development of magnesium cobalt oxide and its composite with reduced graphene oxide for asymmetric supercapacitor applications - Krishnan, Syam G. (2017)
This thesis aims to evaluate the suitability of magnesium cobalt oxide (MgCo2O4) as a pseudocapacitor electrode in asymmetric supercapacitors (ASCs) with improved energy density (ED) and power density (PD). MgCo2O4 belongs to ternary metal cobaltites having desirable electrochemical properties for energy storage devices such as batteries and supercapacitors. In pseudocapacitors, charges are stored at the surface of an electrode by fast faradic reaction and offer improved ED and PD compared to conventional supercapacitors in which charge storage is limited by accumulation at the electrode– electrolyte interface. In this research, three typical morphologies of MgCo2O4 are synthesized using molten salt method (MSM) and hydrothermal method (HT). These synthetic processes offer controllability of properties of the materials thereby produced and scalability of materials production. A high performing ternary metal cobaltite, viz. manganese cobalt oxide (MnCo2O4) is used as a control material owing to its higher theoretical capacitance (~3620 Fg-1) compared to that of MgCo2O4 (~3120 Fg-1) in all the above synthesis. In addition to the pure compounds, their graphene modified analogues are also synthesized. The materials are characterized using thermogravimetric analysis (TGA), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM), and gas surface adsorption techniques. Electrochemical properties of MgCo2O4 and MnCo2O4 are evaluated using cyclic voltammetry (CV), galvanostatic charge-discharge (CD) and electrochemical impedance spectroscopy (EIS) in a three-electrode system using 3 M LiOH as electrolyte. A detailed investigation of the pseudocapacitive performance of the various electrode including the graphene modified ones on the specific capacitance (CS) has been undertaken in threeelectrode configuration. These characterizations revealed the superiority of MgCo2O4 over MnCo2O4 electrodes. Furthermore, performance of graphene modified MgCo2O4 and MnCo2O4 showed superior capacitance of ~570 and ~440 Fg-1, with capacitance retention of 104 and 102%, respectively at the end of 3000 cycles. ASCs are fabricated using graphene modified MgCo2O4 (HS-G-MgCo2O4) and MnCo2O4 (HS-G-MnCo2O4) as anodes and activated carbon (AC) as cathode. A trial and error method is adopted to determine suitable mass loading of the materials in respective electrodes for high ED and PD. Highest ED and PD are obtained for 1:1 wt.% mass loading in anode and cathode. The HS-G-MgCo2O4/AC delivered a maximum ED of ~31.05 Whkg-1 at PD of 1.8 kWkg-1, which is one of the best performances reported for ternary metal cobaltite based ASCs. This research, therefore, identifies a promising pseudocapacitor electrode material for commercial deployment.